Epigenetic Priming of Human Pluripotent Stem Cell-Derived Cardiac Progenitor Cells Accelerates Cardiomyocyte Maturation. (14th May 2019) - Biermann, Mitch; Cai, Wenxuan; Lang, Di; Hermsen, Jack; Profio, Luke; Zhou, Ying; Czirok, Andras; Isai, Dona G.; Napiwocki, Brett N.; Rodriguez, Adriana M.; Brown, Matthew E.; Woon, Marites T.; et al.
Abstract : Human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) exhibit a fetal phenotype that limits in vitro and therapeutic applications. Strategies to promote cardiomyocyte maturation have focused interventions on differentiated hPSC-CMs, but this study tests priming of early cardiac progenitor cells (CPCs) with polyinosinic-polycytidylic acid (pIC) to accelerate cardiomyocyte maturation. CPCs were differentiated from hPSCs using a monolayer differentiation protocol with defined small molecule Wnt temporal modulation, and pIC was added during the formation of early CPCs. pIC priming did not alter the expression of cell surface markers for CPCs (>80% KDR+/PDGFRα+), expression of common cardiac transcription factors, or final purity of differentiated hPSC-CMs (∼90%). However, CPC differentiation in basal medium revealed that pIC priming resulted in hPSC-CMs with enhanced maturity manifested by increased cell size, greater contractility, faster electrical upstrokes, increased oxidative metabolism, and more mature sarcomeric structure and composition. To investigate the mechanisms of CPC priming, RNAseq revealed that cardiac progenitor-stage pIC modulated early Notch signaling and cardiomyogenic transcriptional programs. Chromatin immunoprecipitation of CPCs showed that pIC treatment increased deposition of the H3K9ac activating epigenetic mark at core promoters of cardiac myofilament genes and the Notch ligand, JAG1. Inhibition of Notch signaling blocked the effects of pIC on differentiation and cardiomyocyte maturation. Furthermore, primed CPCs showed more robust formation of hPSC-CMs grafts when transplanted to the NSGW mouse kidney capsule. Overall, epigenetic modulation of CPCs with pIC accelerates cardiomyocyte maturation enabling basic research applications and potential therapeutic uses. Stem Cells   2019;37:910–923 : Abstract : Differentiation of human pluripotent stem cells using a small molecule, biphasic Wnt modulation protocol with polyinosinic-polycytidylic acid treatment to generate primed cardiac progenitor cells that exhibit accelerated differentiation and maturation.